2017
DOI: 10.1111/1462-2920.13798
|View full text |Cite
|
Sign up to set email alerts
|

The ArfGAP protein MoGlo3 regulates the development and pathogenicity of Magnaporthe oryzae

Abstract: The ADP ribosylation factor (Arf) and the coat protein complex I (COPI) are both involved in vesicle transport. Together with GTPase-activating proteins (ArfGAPs) and guanine exchange factors (ArfGEFs) that regulate the activity of Arf, they govern vesicle formation, COPI trafficking, and the maintenance of the Golgi complex. In an ongoing effort to study the role of membrane trafficking in pathogenesis of the rice blast fungus Magnaporthe oryzae, we identified MoGlo3 as an ArfGAP protein that is homologous to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 63 publications
1
23
0
Order By: Relevance
“…graminearum have been verified to be involved in endocytosis and pathogenicity (Dou et al ., ; Zhang et al ., ). Through functional analysis of endocytic proteins such as the ArfGAP protein MoGlo3 (Zhang et al ., ), the class V myosin MoMyo5 (Tang et al ., ), the capping protein MoCap (Li et al ., ), the verprolin protein MoVrp1 (Huang et al ., ), the ADP‐ribosylation factor Arf6 (Zhu et al ., ), the actin‐regulating kinase homologue MoArk1 (Wang et al ., ) and an early endocytic protein‐MoEnd3 (Li et al ., ), it was revealed that endocytosis is essential for conidiogenesis, appressorium formation and pathogenicity in P . oryzae .…”
Section: Discussionmentioning
confidence: 99%
“…graminearum have been verified to be involved in endocytosis and pathogenicity (Dou et al ., ; Zhang et al ., ). Through functional analysis of endocytic proteins such as the ArfGAP protein MoGlo3 (Zhang et al ., ), the class V myosin MoMyo5 (Tang et al ., ), the capping protein MoCap (Li et al ., ), the verprolin protein MoVrp1 (Huang et al ., ), the ADP‐ribosylation factor Arf6 (Zhu et al ., ), the actin‐regulating kinase homologue MoArk1 (Wang et al ., ) and an early endocytic protein‐MoEnd3 (Li et al ., ), it was revealed that endocytosis is essential for conidiogenesis, appressorium formation and pathogenicity in P . oryzae .…”
Section: Discussionmentioning
confidence: 99%
“…cerevisiae Arl1 is Golgi localized (53, 54), we tested whether the punctate colocalizes with the Golgi. To do this, we introduced the Golgi marker protein MoSft2-RFP (MoSft2-red fluorescent protein) (36, 55) and found that the green fluorescence punctate indeed colocalized with MoSft2-RFP in conidia, germ tubes, appressoria, and the vegetative and invasive hyphae (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…We previously found that ArfGAP protein MoGlo3, mediating endocytosis and vesicle trafficking, regulates growth, conidiation, and pathogenesis in the blast fungus (36). Intriguingly, interactions between MoGlo3 and all MoArf proteins cannot be established by the Y2H assay (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Arf6•GTP levels increased by depletion of ACAP3, the shRNA of Arf6 also decreased neurite outgrowth. As the fast cycling mutant of Arf6, T157A rescued the phenotype of ACAP3 knockdown, but not GDP-and GTP-locked mutant of Arf6, Q67L and T44N, Miura et al [33] concluded that the cycle of Arf6 is required for neurite outgrowth. Although the consequences of depletion of ArfGAPs in terms of Arf•GTP levels should be addressed carefully, accumulating evidence [33][34][35][36][37][38][39][40] shows that ArfGAPs are able to positively regulate biological processes.…”
Section: Arfgaps; Depletion or Overexpression?mentioning
confidence: 99%